The Effect of Aerobic Exercise and the DASH Diet on a Sample of Chronic Hypertensive Patients - Hussein, Hassan Adnan (Indonesian Journal Publisher, 2024)
This study examines the effects of aerobic exercise and the DASH diet on chronic hypertensive patients aged 40–50 years. High blood pressure is a widespread chronic condition influenced by genetic, lifestyle, and environmental factors. This research aims to prepare tailored aerobic exercises and implement the DASH diet to evaluate their combined impact on blood pressure management. Using a single-group experimental design, the study involved ten non-athletic male participants with chronic hypertension, selected randomly from Thi Qar Governorate, Iraq. Participants engaged in a 12-week intervention consisting of aerobic exercise and adherence to the DASH diet. Data were collected through pre- and post-tests measuring systolic and diastolic blood pressure. Results revealed significant improvements, with systolic pressure decreasing by 8.7% and diastolic pressure by 8.16%. The study highlights the synergistic effects of physical activity and a healthy diet in reducing blood pressure, underscoring their importance in managing hypertension and improving overall health.